Analisa Hukum Penggugat Menuntut Satu Satunya Ahli Waris dan Warisan di Pengadilan Negeri (Perkara No. 593/Pdt. G/2021/PN.Sby) - Ginah Supriati; Iwan Saputra (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
This study discusses the application of the principle of saisine in Indonesian civil inheritance law, with a case study of Decision No. 593/Pdt.G/2021/PN.Sby. Based on Article 834 of the Burgerlijk Wetboek (B.W.), an heir has the right to claim the entirety of the inheritance property possessed by another party. The aim of this research is to examine the legal basis, the plaintiff’s arguments, and the judge’s considerations in determining the validity of the sole heir status. The research method employed is normative juridical with a case study approach. The results indicate that the plaintiff is entitled to the entire inheritance after being legally proven as the sole heir, through the application of the saisine principle and the provisions regarding the capacity to inherit as stipulated in Articles 838 and 912 of the B.W.